No effect of glutamine supplementation and hyperoxia on oxidative metabolism and performance during high-intensity exercise - Marwood, S.; Bowtell, J. (Journal of Sports Sciences, 2008)
Glutamine enhances the exercise-induced expansion of the tricarboxylic acid intermediate pool. The aim of the present study was to determine whether oral glutamine, alone or in combination with hyperoxia, influenced oxidative metabolism and cycle time-trial performance. Eight participants consumed either placebo or 0.125 g · kg body mass-1 of glutamine in 5 ml · kg body mass-1 placebo 1 h before exercise in normoxic (control and glutamine respectively) or hyperoxic (FiO2 = 50%; hyperoxia and hyperoxia + glutamine respectively) conditions. Participants then cycled for 6 min at 70% maximal oxygen uptake ([Vdot]O2max) immediately before completing a brief high-intensity time-trial (~4 min) during which a pre-determined volume of work was completed as fast as possible. The increment in pulmonary oxygen uptake during the performance test (?[Vdot]O2max, P = 0.02) and exercise performance (control: 243 s, sx = 7; glutamine: 242 s, sx = 3; hyperoxia: 231 s, sx = 3; hyperoxia + glutamine: 228 s, sx = 5; P < 0.01) were significantly improved in hyperoxic conditions. There was some evidence that glutamine ingestion increased ?[Vdot]O2max in normoxia, but not hyperoxia (interaction drink/FiO2, P = 0.04), but there was no main effect or impact on performance. Overall, the data show no effect of glutamine ingestion either alone or in combination with hyperoxia, and thus no limiting effect of the tricarboxylic acid intermediate pool size, on oxidative metabolism and performance during maximal exercise.